2022
DOI: 10.1075/prag.8.1.04hen
|View full text |Cite
|
Sign up to set email alerts
|

Narrative styles of Palestinian Bedouin adults and children

Abstract: This paper contrasts natural oral narratives of Bedouin adults and children (ages 8- 11) in the Negev Desert (South Israel). The analysis showed some striking stylistic differences, on both developmental and genre-related grounds. Adults, narrating tribal legends in a stylized, performed idiom. used distinct styles for the textual levels of orientation, plotline, and direct speech; the children told folktales and anecdotes in a relatively undifferentiated, near-conversational style. Adults set out from a concr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Before we address the impact of language variety on narrative skills, it is noteworthy that even though two of the stories were presented in MSA, participants chose to retell all narratives in PA, including those presented in MSA. This finding accords with earlier reports (Asli-Badarneh et al, 2022; Henkin, 1998; Ravid et al, 2014) and it might reflect the difficulty that children have in producing a text in MSA. Alternatively, children might have been following internalized sociolinguistic patterns of the distribution of codes in Arabic diglossia as it is played out in storybook reading especially in preschool, namely, a text is read/heard in MSA, usually by the teacher or a parent and then paraphrased or retold in PA (Iraki, 1992).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Before we address the impact of language variety on narrative skills, it is noteworthy that even though two of the stories were presented in MSA, participants chose to retell all narratives in PA, including those presented in MSA. This finding accords with earlier reports (Asli-Badarneh et al, 2022; Henkin, 1998; Ravid et al, 2014) and it might reflect the difficulty that children have in producing a text in MSA. Alternatively, children might have been following internalized sociolinguistic patterns of the distribution of codes in Arabic diglossia as it is played out in storybook reading especially in preschool, namely, a text is read/heard in MSA, usually by the teacher or a parent and then paraphrased or retold in PA (Iraki, 1992).…”
Section: Discussionsupporting
confidence: 93%
“…The development of preschoolers' narrative abilities within Arabic diglossia has only rarely been investigated. Henkin (1998) investigated oral narratives of Bedouin from south Israel and showed that when children (aged 8-11) were read stories to in MSA at school, they usually chose to retell these stories in the colloquial dialect. The same finding was observed by Ravid et al (2014) who found that despite the fact that the story was presented to children in MSA, younger children retold the story primarily in the colloquial Palestinian dialect.…”
Section: Narrative Skills In Arabic: the Role Of Diglossiamentioning
confidence: 99%
“…Although there have been a few studies of diverse aspects of children's acquisition of contemporary Arabic (Abu‐Haidar, 1979; Al‐Akeel, 1998; Badry, 1983, 2005; Henkin, 1998; Ibrahim & Eviatar, 2009; Levin, Saiegh‐Haddad, Hende, & Ziv, 2008; Omar, 1973; Saiegh‐Haddad, 2003, 2004, 2005, 2007; Saiegh‐Haddad, et al, 2011), including morphology (Boudelaa & Marslen‐Wilson, 2005) little has been published on the native acquisition of Arabic plural forms.…”
Section: Acquiring the Plural Inflectional System In Arabicmentioning
confidence: 99%
“…Most of the researches so far focused on mapping the Bedouin dialects (Abdel-Massih & Bahig, 1978;Abu El-Hij'a, 2012;Al-Wer & De Jong, 2009;Blanc, 1970;Fischer & Jastrow, 1980;Holes, 1995a;Holes, 1995b;Shawarba, 2007), with specific attention to the Bedouin dialect of the Galilee in north Israel (Rosenhouse, 1980(Rosenhouse, , 1984(Rosenhouse, , 1995a(Rosenhouse, , 1995bRosenhouse & Katz, 1980), the Bedouin dialects of central and southern Sinai (de Jong, 2011), and outside Israel, for example Bedouin dialects in Jordan (Palva, 2008), Egypt and eastern Lybia (Mitchell, 1960), Iraq (Palva, 2009), and Kuwait (Ayyad, 2011); sociolinguistic aspects and stylistic variation of the Bedouin dialects of the Negev (Henkin, 1992(Henkin, , 1994(Henkin, , 1996(Henkin, , 1998(Henkin, , 2000(Henkin, , 2005(Henkin, , 2007a(Henkin, , 2007b(Henkin, , 2009a(Henkin, , 2009b(Henkin, , 2010(Henkin, , 2011; Bedouin poetry (Bailey, 1991;Holes & Abu Athera, 2007;Jargy, 1989); anthropological aspects of Bedouin society (Borg, 1999(Borg, , 2001Borg & Kressel, 1995, 2001; Bedouin manners from socio-linguistic point of view (Piamenta, 1979). However, none of these studies has ever explored aspects of language acquisition and specifically the spelling development of the written form of Arabic among Bedouin students in ...…”
Section: Introductionmentioning
confidence: 99%